1963
DOI: 10.1002/jsfa.2740140207
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of quality in protein concentrates by laboratory procedures involving determination of soluble nitrogen

Abstract: 109 ConclusionsThe synthetic chelating agents used were resistant to nitrification in soils. Application of the acid chelates to soil can considerably modify the concentration of Under the conditions of the experiments described the mineral composition The effect on nutrients in plants. of cabbage plants was considerably more influenced than that of wheat plants. metal concentrations was more marked under alkaline than under acid soil conditions. AcknowledgmentPh.D. in the University of London.This work forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

1964
1964
1988
1988

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…Free-gossypol content and nitrogen solubility in sodium hydroxide are known to be higher in pre-pressed solvent-extracted or direct solvent-extracted cottonseed meal than in the expeller-processed cake and this difference is a direct reflexion of variable heat and pressure generated during oil extraction (Altschul et al 1958). Nitrogen solubility in sodium hydroxide has been used as an index of protein quality and the meal having more than 70 % solubility is accepted as a good quality meal (Lyman, Chang & Couch, 1953;Barnes & Woodham, 1963), although many workers refute this concept (Eagle et al 1956;Eagle & Davies, 1957). In the present study no such relationship was observed between nitrogen solubility and chick growth.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Free-gossypol content and nitrogen solubility in sodium hydroxide are known to be higher in pre-pressed solvent-extracted or direct solvent-extracted cottonseed meal than in the expeller-processed cake and this difference is a direct reflexion of variable heat and pressure generated during oil extraction (Altschul et al 1958). Nitrogen solubility in sodium hydroxide has been used as an index of protein quality and the meal having more than 70 % solubility is accepted as a good quality meal (Lyman, Chang & Couch, 1953;Barnes & Woodham, 1963), although many workers refute this concept (Eagle et al 1956;Eagle & Davies, 1957). In the present study no such relationship was observed between nitrogen solubility and chick growth.…”
Section: Discussioncontrasting
confidence: 55%
“…Available carbohydrate was determined chemically (Clegg, 1956). Nitrogen solubility in acid (6N-HC1), alkaline (0-02 N-NaOH) and saline (0-5 N-NaCl) solutions was also determined (Barnes & Woodham, 1963).…”
Section: Methodsmentioning
confidence: 99%
“…Many additional studies in which a correlation between bird response and nitrogen solubility in alkali ranging from excellent to fair have been reported (Condon et al, 1954;Chang et al, 1955;Grau and Zweigart, 1955;Sasser, 1956;Baliga and Lyman, 1957;Eagle and Davies, 1957;Boyne et al. 1961;Duckworth et al, 1961 ;Stephenson and Greene, 1962;Miner, 1962;Mann et al, 1962;Barnes and Woodham, 1963). Conley et al, (1955) reported a poor correlation between nutritive value and nitrogen solubility when the solubility of the meal exceeded 80 per cent.…”
Section: A Protein Qualitymentioning
confidence: 99%
“…Cottonseed meals have been subjected to several other chemical methods designed to measure protein quality. These include solubility in hydrochloric acid (Boyne et a/., 1961;Anwar, 1962;Barnes and Woodham, 1963), globulin fractionation (Anwar, 1962) and solubility in sodium chloride Condon et al) 1954;Boyne et a/., 1961 ;Anwar, 1962;Barnes and Woodham, 1963).…”
Section: A Protein Qualitymentioning
confidence: 99%
See 1 more Smart Citation